Vibratome sectioning of tumors to evaluate the interactions between nanoparticles and the tumor microenvironment ex-vivo - Liu, Shuhan; Zhang, Juechao; Zhang, Ning-Ning; Meng, Xiandi; Liu, Kun; Yang, Yong-Guang; Sun, Tianmeng; Sun, Liguang (Frontiers in Bioengineering and Biotechnology, 2022)
Nanoparticles have been investigated as drug carriers and promising agents for cancer therapy. However, the tumor microenvironment (TME), which is formed by the tumor, is considered a barrier for nanocarriers to enter the internal tumor tissue. Therefore, the evaluation of the biological distribution of nanocarriers in TME can provide useful information on their role in tumor-targeted drug delivery. Although the tumor-bearing mouse model is commonly used to investigate the distribution of nanocarriers in the TME, there is currently a lack of a testing system to predict the distribution of nanocarriers in tumor tissues, especially in patients. This study revealed that the macrophages and dendritic cells (DCs) were more distributed in the peripheral part than the central part of the tumor, which might be an obstacle to the uniform distribution of nanoparticles in the tumor. In addition, the cellular uptake of gold nanoparticles (AuNR and AuNS) in macrophages and DCs cell lines (RAW264.7 and DC1.2) was markedly different from that in the TME. Hence, the study model of the interaction between nanoparticles and macrophages and DCs has an important impact on the accuracy of the results. The vibratome sections of tumor tissues preserved the spatial distribution of immune cells and tumor cells, and had very little effects on their morphologies and activities. More importantly, we found that the distribution of nanocarriers in vibratome sections was similar to that in tumors in vivo. In all, ex vivo analysis using vibratome sections of tumor tissues provides a more convenient and stable method for elucidating the influences of TME on the distribution of nanocarriers.